Application of the NHT Model to Improve Student Learning Outcomes in Kelas 7 SMP 2 Cokroaminoto Makassar - Subair, Ahmad (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
This study aims to improve history learning outcomes through the Numbered Heads Together (NHT) learning model for seventh grade students at Cokroaminoto Rappokalling Junior High School. This classroom action research was conducted in two cycles, with each cycle including planning, implementation, observation, and reflection. Data were collected through essay test, participation observation, interest questionnaire, and interview. Cycle I results showed 50% student participation and an average test score of 65. After improvements in cycle II (more specific questions, help cards, role play), participation increased to 75% and the average score reached 76. The conclusion of the research proves that NHT is effective in improving cognitive learning outcomes, participation, and student motivation. This study recommends the use of NHT with scaffolding and strict time management for interactive history learning.